Providing incentives for the microelectronics industry as a part of achieving technological sovereignty - V. V. Degtyareva (Управление)
The Government of the Russian Federation is implementing comprehensive measures to counter sanctions, stabilize the economy, restore economic security, and achieve technological sovereignty. Draft laws to close lacunas are being considered, and measures taken to support domestic enterprises in the sphere of economic development priority areas. It is impossible to universally finance a wide range of projects, so the author of the article recognizes expediency of considering prioritization according to certain criteria, such as size of the industry, participation in value chains, efficiency, and operability of the industry at the moment. For the microelectronics industry, it is important to consider state of inter-industry balance indicators to generate orders and maintain economic equilibrium, as its manufactured products are consumed in almost all sectors of the economy due to digitalization penetration at different levels. The purpose of the study is to identify trends in global economy, analyze and predict actions of major players, analyze the Russian microelectronics industry, and rationalize suggestions based on the data collected. The suggestions are to create conditions for innovative development institutions interaction with groups of educational institutions in order to realize joint projects to create innovations. The methodological basis for building the model was provided by modern works in the researched area. The article considers main causes and problems preventing industries from getting out of the critical state within the framework of achieving technological sovereignty, analyzes current state of the microelectronics industry in the current geopolitical situation, and proposes external and internal ways to expand the ‘bottlenecks” in the form of measures to stimulate end-to-end technologies creation.